Manajemen Pendidikan Karakter Berbasis Kearifan Lokal pada Sekolah Menengah Pertama Negeri di Kabupaten Purwakarta - Gianti Gunawan; Yus Nugraha; Marina Sulastiana; Diana Harding (Humanitas (Jurnal Psikologi), 2017)
Implementation of character education based on local wisdom has been implemented in Purwakarta through Sundanese architecture of education buildings, government and public places. Purwakarta also has a policy about 7 special days of education. This research method is descriptive with qualitative approach. Researchers conducted SWOT analysis from character education program based on local wisdom at Junior High School in Purwakarta. Research located at SMPN Kahuripan Purwakarta. Analysis from the research is use to make principes of management by George Terry, including planning, organizing, actuating, and controlling. The methods researc are observation, interview, and quetionaire. The research find that the main obstacle that needs attention is the teacher's readiness / skill. In this case workshops can be conducted to assist teachers about the curriculum, in terms of reducing character education programs based on local wisdom in their respective subjects. Basically they have a positive assessment, it's just a constraint on the application.